Praktik Jual Beli Telur Semut Rang-Rang (Kroto) Di Tinjau Dari Perspektif Hukum Islam (Studi Kasus Toko Burung Senang Hati Kelurahan Parit Culum 1) - Hesti wahyuni; Kurniawan Kurniawan; Reza Okva Marwendi; Haeran Haeran; Nilfatri Nilfatri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the practice of buying and selling rangrang ant eggs (kroto) at the Senang Hati Bird Shop in Parit Culum 1 Subdistrict. This study uses a qualitative approach. Data collection techniques include observation, interviews, and documentation. Based on the findings, the process of selling rangrang ant eggs (kroto) at the Senang Hati Bird Shop involves sales through the shop, local markets, and online platforms. Buyers purchase according to their needs, and prices are set by the seller. The seller sources the kroto from ant hunters who collect them in the forest. The seller sets a high price for kroto due to the risk of loss, as the eggs will hatch into ants over time. From an Islamic legal perspective, while there is no fixed maximum limit for profit-taking, a blessed profit is considered to be one that does not exceed one-third of the capital price. Therefore, the practice of buying and selling rangrang ant eggs (kroto) at the Senang Hati Bird Shop in Parit Culum 1 is considered valid according to Islamic law, as it does not contradict its principles.